Numerical computational approach for 6th order boundary value problems - Adebisi, Folasade Ajimot; Ishola, Christie Yemisi; Uwaheren, Ohigweren Airenoni; Okunola, Kamilu Adedokun; Raji, Musiliu Tayo; Oseni, Wasiu (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
This study introduces numerical computational methods that employ fourth-kind Chebyshev polynomials as basis functions to solve sixth-order boundary value problems. The approach transforms the BVPs into a system of linear algebraic equations, expressed as unknown Chebyshev coefficients, which are subsequently solved through matrix inversion. Numerical experiments were conducted to validate the accuracy and efficiency of the technique, demonstrating its simplicity and superiority over existing solutions. The graphical representation of the method's solution is also presented.